Association between mortality among women and socioeconomic factors in general practices in Edinburgh: an application of small area statistics. Issue 6601 (26th September 1987) - Alexander, F E; O'Brien, F; Hepburn, W; Miller, M
Abstract : Women aged 45-64 in 78 general practices in the city of Edinburgh were followed up for five to seven years and all cause mortality noted. Standardised mortality ratios were calculated for the individual practices. Postcodes were available for a 20% sample of these women and were used to retrieve relevant measures of social class and deprivation from the 1981 census for the smallest division, the enumeration district. Weighted averages gave socioeconomic variables at the level of the general practice. High positive correlations were found between standardised mortality ratios and the socioeconomic variables, with the highest being for percentage overcrowding. This study established that the relation between deprivation and excess mortality can be shown in general practices in one large city and gave a direct relation for women without reference to their husbands' occupations, thus obviating problems of assigning social class. The data also partially refute the "social drift" hypothesis as an explanation of the association between mortality and social class.